Landowners' Perceptions of Conservation Easements: Implications for Effective Persuasive Communication - Caitlin Cooper; Jefferson D. Miller; Shane White; Lauren Gwaltney (Journal of Applied Communications, 2023)
Conservation easements (CEs) are one of the most popular voluntary, legally binding programs that allow individual landowners to use their property to protect the environment. There is a definite need for educational and persuasive messaging targeted towards landowners regarding adopting conservation easements. Based on previous studies, and confirmed by this study, communication efforts that are led by conservation experts who are also community members are most likely to be well received by landowners in a region. There is currently little to no existing region-specific literature specifically related to the attitudes and behaviors landowners possess towards conservation easements. Additionally, more literature is needed regarding landowners’ communications preferences for learning about CEs; the existing literature focuses broadly on environmental communication. This study aimed to fill a gap in literature by conducting a quantitative survey and qualitative phone interview with landowners in Northwest Arkansas and Northeast Oklahoma. Participants were asked to identify their awareness level knowledge about conservation easements, as well as rank incentivizing and disincentivizing factors that would influence their decision to adopt conservation easements. Researchers identified that there is a strong need for regional easement organizations to increase their awareness-level educational communications efforts. In addition, participants noted a strong desire for more personalized and in-person communications methods to be used by easement organizations.
Keywords: Conservation easement; landowner; land conservation; sustainability; theory of planned behavior; communication; conservation marketing